Przez kogo mówi do nas rzeczywistość? Formy wieszczowania w starożytnych Indiach (Przegląd Religioznawczy – The Religious Studies Review, 2023)
In this article, the issue of prophets and soothsayers suggested in the title of this volume is presented in the oldest Indian tradition based on the Vedic canon – śruti. It was assumed that a specific ontological model should be taken into account, and the concept of a prophet or a soothsayer refers more to a function, a certain phenomenon, and not a person as such. The śruti canon was a subject of various transformations during its formation and the original framework of orthodoxy was loosened. The same is true of the earliest understanding of who and later of what the soothsayers were. The article discusses the main phenomena related to this issue. The role of Vedic seers can be assumed in the first place by men originating from Brahmin varna, then by Kshatriyas, and later by men of undefined social status, and even by women. Various animals as well as the forces of nature can also express the power of soothsaying. In the final stage the reality itself can send special signs.